New Insights Into Tissue Culture Plant-Regeneration Mechanisms - Long, Yun; Yang, Yun; Pan, Guangtang; Shen, Yaou (Frontiers in Plant Science, 2022)
Plant regeneration occurs when plants repair or replace damaged structures based on the totipotency and pluripotency of their cells. Tissue culture is one of the most widely used regenerative technologies. Recently, a series of breakthroughs were made in the study of plant regeneration. This review summarises two regenerative pathways in tissue culture: somatic embryogenesis and de novo organogenesis. Furthermore, we review the environmental factors influencing plant regeneration from explant sources, basal culture medium, plant growth regulators, and light/dark treatment. Additionally, we analyse the molecular mechanisms underlying somatic embryogenesis and de novo organogenesis. This knowledge will promote an understanding of the fundamental principles of plant regeneration from precursor cells and lay a solid foundation for applying plant micropropagation and genetic modification.